Biogeochemical validation of an interannual simulation of the ROMS-PISCES coupled model in the Southeast Pacific - Espinoza-Morriberon, Dante (2016)
Currently biogeochemical models are used to understand and quantify key biogeochemical processes in the ocean. The objective of the present study was to validate predictive ability of a regional configuration of the PISCES biogeochemical model on main biogeochemical variables in Humboldt Current Large Marine Ecosystem (HCLME). The statistical indicators used to evaluate the model were the bias, root-mean-square error, correlation coefficient and, graphically, the Taylor’s diagram. The results showed that the model reproduces the dynamics of the main biogeochemical variables (chlorophyll, dissolved oxygen and nutrients); in particular, the impact of El Niño 1997-1998 in the chlorophyll (decrease) and oxygen minimum zone depth (increase). However, it is necessary to carry out sensitivity studies of the PISCES model with different key parameters values to obtain a more accurate representation of the properties of the Ocean.